2019
DOI: 10.1002/gps.5101
|View full text |Cite
|
Sign up to set email alerts
|

Predicting admission to long‐term care and mortality among community‐based, dependent older people in Ireland

Abstract: Objective To identify factors that predict admission to long‐term care (LTC) and mortality among community‐based, dependent older people in Ireland, who were in receipt of formal home support. Methods An audit was conducted of all community‐dwelling older adults receiving government funded home support during 2017 in the Dublin North Central, Health Service Executive administrative area. Data were extracted from the Common Summary Assessment Report (CSAR), a mandatory form used in the provision of home support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 38 publications
3
53
0
Order By: Relevance
“…The importance of cancellations stems from the potential consequences of healthcare deprivation, while the number of weekly care hours has been shown to predict admission to long-term care facilities especially in the older population. 4 …”
Section: Introductionmentioning
confidence: 99%
“…The importance of cancellations stems from the potential consequences of healthcare deprivation, while the number of weekly care hours has been shown to predict admission to long-term care facilities especially in the older population. 4 …”
Section: Introductionmentioning
confidence: 99%
“…Dementia disorders are typically progressive, leading to dependency and death [1][2][3], and progression of dementia is associated with numerous factors [4][5][6]. Prognosis is of key importance for newly diagnosed persons with dementia and their families, especially in regard to the amount of time to dependency and the need for around-the-clock assistance.…”
Section: Introductionmentioning
confidence: 99%
“…Both time to dependency and time to mortality in persons with dementia are associated with older age, poorer cognition and reduced functioning in activities of daily living (ADL) at the time of diagnosis [1,[4][5][6][23][24][25]. As functional and cognitive impairment progress during the course of dementia, support at home provided by formal carers or family members may delay NH admission [5,10,26]. Studies have indicated that married persons or persons with adult children are less likely to be admitted to NHs, probably because of the support they receive at home [10,[27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed how these outcomes varied by already established factors contributing to health inequalities. The importance of cancellations stems from the potential consequences of healthcare deprivation, while the number of weekly care hours has been shown to predict admission to long-term care facilities especially in the older population 4 .…”
Section: Introductionmentioning
confidence: 99%